Avaliação da implantação da iniciativa hospital amigo da criança no Rio de Janeiro, Brasil An evaluation of the implantation of the baby-friendly hospital initiative in Rio de Janeiro, Brazil - Maria Inês Couto de Oliveira; Zulmira Maria de Araújo Hartz; Vivianne Cavalcanti do Nascimento; Kátia Silveira da Silva (Instituto Materno Infantil de Pernambuco, 2012)
OBJETIVOS: avaliar a implantação da Iniciativa Hospital Amigo da Criança no Rio de Janeiro. MÉTODOS: pesquisa avaliativa realizada em 2009, com sete hospitais credenciados (HAC) e oito não (HNC), do SUS. Avaliação de estrutura (Passos 1 e 2) realizada por observação e entrevista a 215 profissionais. Avaliações de processo (Passos 3 a 10) e resultado compreenderam entrevista em amostra representativa de 461 gestantes, 687 mães em alojamento conjunto e 148 mães com recém-nascido em unidade neonatal. O grau de implantação foi avaliado segundo o cumprimento de cada passo e de parâmetros compreendidos nestes passos. A correlação entre grau de implantação e desfechos foi analisada por meio de regressão linear: aleitamento materno (AM) na primeira hora, AM exclusivo (AME) e satisfação das mulheres com o apoio recebido. RESULTADOS: os graus de implantação variaram de 9 a 5 passos (90,6% a 70,1% dos parâmetros) cumpridos nos HAC e de 5 a 1 passo (76,1% a 43,9% dos parâmetros) nos HNC. Foi encontrada correlação linear significativa entre o grau de implantação, expresso em passos e parâmetros, respectivamente, e o AM na primeira hora (r=0,78 e r=0,74), o AME (r=0,72 e r=0,69), e a satisfação (r=0,69 e r=0,73). CONCLUSÕES: ambas as formas de avaliação mostraram-se consistentes com os resultados. Os HAC apresentaram um desempenho superior aos HNC, sendo necessário um investimento na sustentabilidade desta iniciativa. OBJECTIVES: to evaluate the implantation of the baby-friendly hospital initiative in Rio de Janeiro. METHODS: an evaluative study was carried out in 2009 at seven baby-friendly hospitals (BFHs) and eight non-accredited hospitals (NAHs) forming part of the Brazilian National Health System. Evaluation of the structure (Steps 1 and 2) was carried out by way of observation and interviews with 215 staff members. Evaluation of the process (steps 3 to 10) involved interviews with a representative sample of 461 pregnant women, 687 mothers on the wards and 148 mothers with a newborn in a neonatal unit. The degree of implantation was assessed in terms of the fulfillment of each step and the parameters covered by it. The correlation between the degree of implantation and outcomes was analyzed using linear regression: breastfeeding (BF) in the first hour of life, exclusive breastfeeding (EBF) and the satisfaction of the women with the care provided. RESULTS: the degree of implantation varied from 9 to 5 steps (90.6% to 70.1% of parameters) completed at the BFHs and 5 to 1 steps (76.1% to 43.9% of parameters) at the NAHs. A significant linear correlation was found between the degree of implantation, expressed in terms of steps and parameters, respectively and BF in the first hour of life (r=0.78 and r=0.74), EBF (r=0.72 and r=0.69), and satisfaction (r=0.69 and r=0.73). CONCLUSIONS: both forms of evaluation were shown to be consistent with the results. The BFHs performed better than the NAHs and there is therefore a need for investment in the sustainability of this initiative.